PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN MODAL KERJA TERHADAP LIKUIDITAS PADA PT. MANDOM INDONESIA TBK PERIODE 2012-2021 - Hestu Nugroho Warasto; Janudin Janudin; Sinta Baharani (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the partial and simultaneous influence of variables of Cash Turnover, Receivables Turnover, and Working Capital Turnover on PT Mandom Indonesia Tbk's Liquidity in 2012 – 2021. The research method used is a quantitative method with a type of quantitative descriptive method research. The data used in this study are financial statements sourced from the official website of PT Mandom Indonesia Tbk. Data analysis techniques use classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis tests using SPSS version 26. The results of the study based on the partial test showed that cash turnover had a calculated value of (-2,864 > 2,447) and a significance value of 0.021 < 0.05. So it can be concluded that cash turnover has a negative and significant effect on liquidity. Receivables turnover has a calculated value of (-3,961 > 2,447) and a sigifikansi value of 0.004 <0.05. Then it can be concluded that the turnover of receivables has a negative and significant effect on liquidity. Working capital turnover (X3) has a calculated value of (-4.242 > 2.447) and a significance value of 0.003 < 0.05. So it can be concluded that the turnover of working capital has a negative and significant effect on liquidity. Simultaneously cash turnover, receivables turnover and working capital turnover to liquidity where the calculation > ftable is (7,732 > 4,757) then Ho4 is rejected and Ha4 is accepted. The significance value is 0.017 < 0.05, meaning that there is a simultaneous positive and significant influence between cash turnover, receivables turnover and working capital turnover on liquidity at PT Mandom Indonesia Tbk